A contribution to Macrolasia Weise (Coleoptera: Coccinellidae: Epilachnini) - Szawaryn, Karol; Tomaszewska, Wioletta (Zootaxa, 2014)
A detailed morphological re-description of the Indian genus Macrolasia Weise, 1903 is given. First drawings of genitalia, SEMs and color photographs are included. A distribution map of the genus Macrolasia is provided. A lectotype of Macrolasia arcula Weise is designated.